Evidence for circular permutation of the prophage genome of Bacillus subtilis bacteriophage phi 105. - Marrero, R (1986)
Analysis of DNA extracted from Bacillus subtilis lysogenic for bacteriophage phi 105 was performed by restriction endonuclease digestion and Southern hybridization using mature phi 105 DNA as a probe. The data revealed that the phi 105 prophage is circularly permuted. Digests using the enzymes EcoRI, SmaI, PstI, and HindIII localized the bacteriophage attachment site (att) to a region 63.4 to 65.7% from the left end of the mature bacteriophage genome. The phi 105 att site-containing SmaI C, PstI J, and HindIII L fragments were not present in digests of phi 105 prophage DNA. phi 105-homologous "junction" fragments were visualized by probing digests of prophage DNA with the purified PstI J fragment isolated from the mature bacteriophage genome. The excision of the phi 105 prophage was detected by observing the appearance of the mature PstI J fragment and the concomitant disappearance of a junction fragment during the course of prophage induction.